Fiscal reforms in Thailand - Chow, Yew Shiong (2013)
The fiscal crisis facing most developing countries and the corresponding problems of resource mobilization, external debt and widening savings-investment gap have directed new attention to the importance of sound fiscal policies over the past few years. Like many other developing countries, Thailand was unable to escape from the aftermath of the fiscal crisis. Hence, to cure the country of its economic ills, the Thai government shifted more emphasis towards restructuring its fiscal system, with the aim of achieving economic stability. As result, Thailand’s economy improved significantly and its growth rate began to increase rapidly. Despite these seemingly favourable developments, Thailand was once again forced with severe economic problems due to occurrences of various external events. Major structural weaknesses in the fiscal system surfaced in the light of these problems, thereby signalling the urgent need for further reform.